The sheep, the rooster, and the duck - Phelan, Matt (Greenwillow Books, 2022)
A seasoned group of crime fighters--a sheep named Bernadette, a rooster named Pierre, and a duck named Jean-Luc--get wind of a plot by the nefarious magician Cagliostro to use one of Benjamin Franklin's inventions to take over America. Unwittingly caught up in the middle of the mayhem is Emile, the devoted caretaker of Franklin's estate. Emile is shocked to discover the spy organization has its headquarters at the estate, but upon learning that Franklin and an important invention have gone missing, he joins the trio in a high-stakes adventure to stop Cagliostro.